Determinants of Innovative Activity in Newly Founded Knowledge Intensive Business Service Firms - Andreas Koch; Harald Strotmann (Institut für Angewandte Wirtschaftsforschung (IAW), 2005)
Innovative activity is performed to a considerable extent in the service sector, namely within the socalled knowledge intensive business services (KIBS). Nevertheless, little is known about the determinants of innovative activity in these firms. In the present paper, some of these determinants are examined on the basis of a recently created dataset of 547 newly founded German firms (KIBS Foundation Survey 2003). The results show that the access to knowledge through cooperation and networking is an important factor determining innovative activity in the KIBS sector, whereas, surprisingly, neither managerial characteristics nor spatial proximity have general influence.
Keywords: L89; D83; O31; 330